Screening for Autism Spectrum Disorder Among Toddlers age children visiting Dr. Jamal Ahamed Rashid Pediatric Teaching Hospital in Sulaymaniyah City / Iraq - Nasradeen Majeed, Bahar (Journal of Neonatal Surgery, 2025)
Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social communication and the presence of restricted interests and repetitive behaviors. It is diagnosed by observing deficiencies in behavior in three areas: social interaction, communicative ability and the range of activity and interests. Aim of the study: This study aims to identify risk of autism spectrum disorder among toddler’s age patients visiting pediatric hospital through using screening tools (M- CHAT-R/F). Methodology: A descriptive study was conducted in Dr. Jamal Ahamed Rashid Pediatric Teaching Hospital during the period 1st February2024 to 30th October 2024. 200 pediatric patients with their mothers were selected to participate in the current study, data collection done by interviewing with each participant through using a questionnaire form consisting of two parts: the first part consist of 4 items related to the child characteristics like (Age of the child, its gender, gestational age and types of delivery), and also 4 items related to the mothers like (age of the mother, the place of residence, level of education and marital status). Second part of questionnaire form is a standard tool for screening autism spectrum disorder among children which consists of 20 questions. Results: The main findings are majority of children were in the second years of age, related to gender more than half of sample 58.5% were male, highest percentage of children their gestational age was full-term, and proportion of normal delivery and caesarian section approximately equal. Related to mother’s characteristics highest percentages of mothers 59.5% their age ranged between 21-30 years old, and lived in inside the city. 55% of mothers were graduated from colleges and 77.5% were married or living together. The current study found that 93.5% of toddlers have low risk of autism spectrum disorder, 5.5% have moderate risk of autism spectrum disorder, and only 1% of children have sever risk of autism spectrum disorder. Conclusions: based on findings researcher concluded that majority of toddlers in current study were at low risk of autism spectrum disorder (ASD), and high risk for autism spectrum disorder record the lowest percentages. Recommendation: further studies on larger sample to screening autism spectrum disorder among toddlers and preschool age children for early detection and promoting early intervention and supportive services for children with autism and their families.